TATA KELOLA PEMERINTAHAN DESA BINA BARU BERBASIS E-GOVERNMENT DALAM MENINGKATKAN PELAYANAN PUBLIK DI ERA INDUSTRI 4.0 - Sartika Amiruddin; Herman Dema; Haeruddin Syarifuddin (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the governance of Bina Baru Village, Kulo District, based on E-Government in improving public services in the Industrial Era 4.0 and to find out the inhibiting factors for E-Government-based public services in the Industrial Era 4.0 in Bina Baru Village, Kulo District, Sidenreng Rappang Regency. . The research population was 329 people/person and the sample was 49 people/person. The sampling technique used is purposive sampling. This type of research is descriptive quantitative. The data collection techniques used are observation, library research, questionnaires or questionnaires and documentation. The data analysis technique is in the form of descriptive statistics. The results showed that 66% of E-Government-based governance was